Governing climate mobility: A scoping study of two localities in Ethiopia - Dessalegn Rahmato; Zerihun Mohammed; Neil Webster (Danish Institute for International Studies (DIIS), 2021)
Climate change is widely expected to produce new and/or intensified mobility patterns, including migration and displacement. However, research on the relationship between climate change and human mobility is limited, especially regarding the roles of governance and interventions in shaping mobility responses. The Governing Climate Mobility (GCM) Research Programme seeks to address this gap by examining the relationships between climate change, mobility and governance in Ghana and Ethiopia. This DIIS Working Paper is a scoping study of the programme's case-study areas in the South Wollo and West Arsi Zones in Ethiopia. It provides data and analysis on a range of relevant environmental, socioeconomic, governance and mobility characteristics that are present in each locality. This includes multi-decadal analyses of changes in temperature, rainfall and vegetation, links between them and how they are experienced locally, and existing contexts of governance and mobility. It builds on a previous GCM working paper on the historical links between climate, mobility and governance in Ethiopia (DIIS WP 2020: 05) and identifies the key dynamics of mobility, climate change and governance that can be taken up in forthcoming studies within the GCM programme.
Keywords: 330; Natural resources and environment; Climate change and environment; Migration and development; Development in practice; Ethiopia